Plant-derived pyroptosis inducers as a therapeutic strategy in drug-resistant cancers - Kang Zi Khor; Adam Azlan; Nozlena Abdul Samad; Emmanuel Jairaj Moses; George George Mathew; Julia Joseph (Springer Nature, 2025)
Drug resistance in cancer therapy, often due to the evasion of apoptosis, highlights the need for alternative treatments. Pyroptosis is a type of inflammatory programmed cell death mediated by gasdermin proteins. It offers a promising approach as it can trigger anti-tumour immunity through cytokine release. Plant-derived compounds, rich in bioactive metabolites, can induce pyroptosis via inflammasome activation, gasdermin cleavage and reactive oxygen species (ROS) generation. Phytochemicals like curcumin, quercetin, cucurbitacin B and kaempferol selectively target cancer cells while modulating inflammation in healthy tissues. Combining these compounds with chemotherapy, immunotherapy or nanoparticle-based delivery systems enhance their therapeutic efficacy and overcome drug resistance. Despite promising preclinical findings, clinical translation remains challenging, necessitating further research to optimise safety, specificity, and delivery mechanisms. This review consolidates current knowledge on plant-derived pyroptosis inducers, highlighting their mechanisms, therapeutic potential, and future directions in combating drug-resistant cancers.